Development of a Sanitation Education Program in Communities Near the Ganges River - Uma Shankar Yadav; Tamrin Fathoni; Lisma Meilia Wijayanti (International Assulta of Research and Engagement (IARE), 2023)
The purpose of writing this work is to describe the Development of a Sanitation Education Program in Communities Near the Ganges River. We propose an ABCD (Asset-Based Community Development)-based sanitation education program for communities around the Ganges River, India, involving participatory data collection techniques and training in healthy sanitation practices. This program involves community members, support teams, local governments and NGOs to achieve cleanliness and sustainability goals. The result of this work is that In communities around the Ganges River that have long struggled with complex sanitation problems, they have developed an ambitious Sanitation Education Program. This program is supported by field data and relevant theory, with a focus on developing a Sanitation Education Module that is comprehensive and easy to understand. They also recognize the importance of training local teaching staff and mentoring the community to actively participate in the program. This approach reflects the theories of community building, transformational leadership, and behavior change. Lastly, the integration of sanitation education in formal and informal education systems ensures the program's sustainability and positive influence on future generations.